Development and Validation of Modified Strategic Intervention Materials as Self-Learning Materials for the New Normal in Education - Pecson, Ryan (Asian Journal of Applied Education (AJAE), 2026)
Developing self-learning materials (SLMs), like strategic intervention materials (SIMs), helps reinforce learning and build learner independence. This study focused on creating modified SIMs (MSIMs) to support senior high school (SHS) learners in the subject Disciplines and Ideas in the Social Sciences (DISS) for Humanities and Social Sciences (HUMSS) strand in the Philippines. Using the descriptive developmental design or DRR (Design and Development Research) of quantitative research approach, the researcher assessed 75 SHS learners with a 30-item pre-test to find areas where they struggled most. At the same time, the 15 expert teachers evaluated the MSIMs using a survey questionnaire. The researcher-made survey questionnaire was validated by three expert validators and subjected to a dry run with five SHS teachers handling DISS, yielding a reliability index of α=0.9923 (excellent). The MSIMs were then developed from the least-mastered competencies and validated by expert teachers. Results were analyzed with descriptive statistics (i.e., frequency, percentage, mean, and standard deviation). Three MSIMs were developed to address the least-mastered competencies of learners. They were rated as acceptable and valid by expert teachers, making them viable alternatives and supplementary materials for remediation. It is recommended that more MSIMs be developed in other learning areas and subjects through action research to test their effectiveness once used among learners.